KORELASI ANTARA BOBOT BADAN DENGAN LINGKAR DADA KAMBING KEJOBONG DI KTT NGUDI DADI PURBALINGGA - Dewi Puspita Candrasari; Agus Susanto; Setya Agus Santosa; Dattadewi Purwantini; Hermawan Setyo Widodo; Chomsiatun Nurul Hidayah (Fakultas Peternakan Universitas Jenderal Soedirman, 2022)
Background. Local goats are widely cultivated in Indonesia, especially in Kejobong, Purbalingga. Local farmers usually determine the price of livestock from body weight. To make it easier, it can be done by measuring the chest circumference, which is quite accurate compared to the results of the scales. The purpose of the study was to estimate the body weight (BW) of Kejobong goats using chest circumference (LD) measurements. The purpose of this study was to estimate the body weight (BB) of Kejobong goats using chest circumference (LD). The materials used were 38 female Kejobong goats aged 3-12 months and 51 heads >12-30 months. Samples were taken using purposive random sampling. The variables observed were the BB and LD of female Kejobong goats. The calculation results show a correlation (r) in the age group 3-12 months of 0.984, in the age group >12-30 months the correlation is 0.691 and in all age groups of 0.942. The results of the correlation between LD and BB obtained a linear regression equation for female Kejobong goats aged 3-12 months Y= -21.433+0.6552x, in the age group >12-48 months Y= -21.916+0.735x and in all age groups Y= -28.802+0.812x. The linear regression equation can be used to estimate the body weight of female Kejobong goats at all ages.